DistilWise IoT: A Smart Industrial Wastewater Treatment innovation by UMPSA researchers - Nur Hartini, Mohd Hatta (UMPSA, 2025)
PEKAN, 16 July 2025 – A team of researchers from the Faculty of Civil Engineering Technology (FTKA), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), led by Associate Professor Dr. Nadzirah Mokhtar, has successfully developed an innovative water treatment system that integrates membrane distillation technology with the Internet of Things (IoT).